(3McGjJj aj Jd CHjHs (3CSQGQ OHdheGSj eUQjs - (3GdCfUGQj, QaYJs ((3GdbGgQIs (3GdOGQ GdeUQjI GddHfGfjIs, 2015)
(3jOhQ McGjJi ai Jd GHjH Hjf GdeNGWQ hGdTc GdPi jQhi ajg cGJHg GdSajQ QaYJ GdGfUGQi McGjJg ai Jd GHjH, Mjf cGf jYed ai SaGQI eUQ gfGc, abO Je hVYg JMJ GdeQGbHI efP dMXI hUhdg ef bHd GLgRI GdGef GdGSQGFjdi hNGUI GdehSGO hGdTjf HjJ (B- (3hbGeJ HQUOg WhGd aJQI Yedg dGUWjGOg hYfOeG aTdJ ai Pdc bQQJ Gf Jchf GdehGLgI GdMGSeI, MjK MGhdJ GZJjGdg KdGK eQGJ ddJNdU efg fgGFjG (B.. (3hGeG deGPG NUJg GLgRI GdGef GdGSQGFjdjI HgPG GdbOQ ef GdTc hGdJQHU, aGdGLGHI SgdI, jQhjgG dfG GdGfUGQi ai (B" (3McGjJi ai Jd GHjH (B" (3hGdPi jcTa ajg QaYJ GdGfUGQi Yf LGfHG egeG ef MbjbI GdeLJeY GdGSQGFjdi ai GdaJQI GdJi Yed HgG gfGc, ceG jaVM GSdhH GdeNGHQGJ GdGSQGFjdjI ai GdGZJjGdGJ hJfajP GdYedjGJ GdYOGFjI hgh GdGSdhH GdPi de jJZjQ QZe eQhQ GdSfjf, jYQi GdGfUGQi ai cJGHg (B" (3McGjJi ai Jd GHjH (B" (3GdeLJeY GdGSQGFjdi ef NdGd YdGbGJg GdhWjOI GdJi GbGegG eY GdGSQGFjdjjf hGdGSQGFjdjGJ hGdJi GSJWGY ef NdGdgG cTa eNWWGJ GSQGFj GdYOGFjI JLGg GdYQHs
(3eJhGaQ efg GdWHYI GdKGdKI dYGe (B2015 (3HecJHI eUQ GdYGeI aQY GdhGOj GdLOjOs
(3eJhGaQ efg GdWHYI GdKGfjI dYGe (B2015 (3HecJHI eUQ aQY GdRGhjI GdMeQGAs
1 2 4 7 12 13 14
NEW, HISTORY_G
Keywords: (3GdOHdheGSjhfs -- (3JQGLes; (3GdedMbhf GdOHdheGSjhfs